2019
DOI: 10.3390/sports7020038
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Anthropometric Measures of Young Brazilian Judo and Wrestling Athletes and Its Relations to Cardiorespiratory Fitness

Abstract: This study aimed to compare the anthropometric profile and physical fitness of young judo and wrestling athletes. Twenty-four young athletes (judo (n = 13) and wrestling (n = 11)) participated in this study. The first visit involved anthropometric and flexibility evaluation, abdominal endurance test, upper limbs resistance and cardiorespiratory test. After 48 h, horizontal jump test (HJT), vertical jump test (VJT), medicine ball throw test (MBT), chin-up test (CUT), chin-up isometric test (CUIT) and the anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
6
0
3
Order By: Relevance
“…It has been shown that there is an inverse relationship between flexibility and SJFT index, meaning that the higher the flexibility, the better the performance in SJFT (Arazi, Noori and Izadi 2017). Although insufficient information exists regarding the flexibility of judo athletes, the flexibility the Saudi judo athletes determined in this study (35 cm) was similar to those reported by Marques et al (2019). However, Arazi et al (2017) found greater values for the flexibility in their judo athletes (48 cm) than of those in our study.…”
Section: Resultssupporting
confidence: 83%
“…It has been shown that there is an inverse relationship between flexibility and SJFT index, meaning that the higher the flexibility, the better the performance in SJFT (Arazi, Noori and Izadi 2017). Although insufficient information exists regarding the flexibility of judo athletes, the flexibility the Saudi judo athletes determined in this study (35 cm) was similar to those reported by Marques et al (2019). However, Arazi et al (2017) found greater values for the flexibility in their judo athletes (48 cm) than of those in our study.…”
Section: Resultssupporting
confidence: 83%
“…It can be seen from the competitions of various sports that the athletes or sports teams with superior skills cannot win the final victory, which is often due to the lack of physical ability, especially when the level is extremely close [1]. According to the classic event group training theory, football belongs to the same field antagonistic event dominated by skills, and the dominant factor determining its competitive level is skills [2].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of muscular endurance and the ability to maintain high levels of muscular strength, strength and speed in combat can contribute to the performance and efficiency of an appropriate motor gesture, thus contributing to improving the technicaltactical performance of athletes." (Marques et al, 2019) According to Ratamess (2011, 21), "weight training is a staple of grappler training for at least 3-4 workouts per week. Exercises should be selected from 3 broad categories: Olympic-style/power lifts, basic strength, and auxiliary exercises" for senior fighters, this being similar to our experimental approach adapted to the age category of our sample, while also taking into account "sequencing exercises between upper-and lower-body and/or agonist/antagonist muscle groups is also effective" (Ratamess et al, 2009).…”
Section: Discussionmentioning
confidence: 99%